Analisis Hukum Internasional Terhadap Perlindungan Underwater Cultural Heritage di Wilayah Perairan Dalam Yurisdiksi Nasional - Wulandari, Annindya Jasmine; Puspitawati, Dhiana; Madjid, Yasniar Rachmawati (RechtJiva, 2026)
This study addresses the issue of legal uncertainty regarding the protection of underwater cultural heritage (UCH) in waters under national jurisdiction, resulting from the absence of detailed provisions on the protection of UCH in such waters under national jurisdiction in the 1982 UNCLOS, which has led to legal uncertainty. UCH is regulated by the UCH Convention, which addresses the legal uncertainty regarding UCH protection in UNCLOS 1982. In this context, non-member states of the UCH Convention face legal uncertainty regarding the protection of UCH in waters under national jurisdiction, particularly regarding the argument that UCH can be “equated” with natural resources. Based on this, this research raises the following research questions: (1) How is the protection of UCH regulated under international law? (2) How is the legal protection of UCH in waters under national jurisdiction conceptualized, specifically, can UCH be considered a natural resource? This research employs a normative legal methodology using a statutory approach and an analytical approach, and analyses legal materials using qualitative methods. Research findings indicate that the international legal framework governing UCH, as established under UNCLOS 1982, is too ambiguous to provide a valid legal basis for the protection of UCH. The provisions of the UCH Convention comprehensively address the protection of UCH. The concept of legal protection for UCH in waters under a state’s national jurisdiction, as outlined in the UCH Convention, does not classify UCH as a natural resource. The UCH Convention has specifically provided a concept of protection for UCH in waters under national jurisdiction. Therefore, it is important for countries around the world to carry out the ratification procedures for this convention.